Agronursing Approaches in Supporting the Mental Health of Agricultural Workers - Nabila Puspita Dewi; Adisyah Maulidina Safi’i; Dynta Eka Anggraeni; Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi (KHD Production, 2025)
Agricultural workers face complex work pressures such as social isolation, weather dependency, and limited access to health services, which impact their mental health. Agronursing is emerging as a nursing approach that is responsive to the specific needs of agrarian communities in a holistic and culturally based manner. This article explores the role of agronursing in supporting farmworkers' mental health through contextualized and sustainable interventions. This literature review employed a systematic search in ScienceDirect, PubMed, and MDPI databases for articles published between 2020 and 2025. From 4,371 identified articles, a multi-stage screening and eligibility process was conducted, resulting in 10 articles that met all inclusion criteria for final analysis. Burnout and mental health problems are prevalent among agricultural workers due to various internal and external stressors. Various approaches, such as increasing psychological and social capital, self-coping strategies, and multimodal interventions, have proven effective in maintaining farmers' mental well-being. An agronursing perspective and community support are important in sustainably building farmers' psychological resilience. Farmers' mental health is adversely affected by economic stress, overwork, and social isolation, with stigma and mistrust hindering access to support. Effective interventions must be context-sensitive and involve farmers to ensure psychological impact and community acceptance.